2017
DOI: 10.1590/0034-7167-2017-0089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supportive telephone counseling in the metabolic control of elderly people with diabetes mellitus

Abstract: Objective: the purpose of this study was to evaluate the efficacy of telephone-based support for the metabolic control of elderly patients with diabetes mellitus. Method: a pragmatic study was conducted in two groups, called G1 (n=36) and G2 (n=27), at a health unit from the countryside of São Paulo state. Patients in G1 group received telephone support over four months, through 16 telephone contacts with educational material; for the G2 group the educational material was mailed. Results: significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 20 publications
0
13
0
8
Order By: Relevance
“…The participants in our study had low levels of education, which may have impaired their access to information and hindered their self-care, in addition to making it difficult to adhere to the treatment required concerning their comorbidities. Becker (2017) suggested that telephone contact was an efficient means of health education for this vulnerable population [9], and it appears reasonable to continue with this type of care when aiming to clarify issues and challenges concerning COVID-19. In addition, telehealth was effective in improving glycemic control, blood pressure, and knowledge about type 2 diabetes mellitus in a clinical trial with diabetic and hypertensive elderly individuals [10].…”
Section: Discussionmentioning
confidence: 99%
“…The participants in our study had low levels of education, which may have impaired their access to information and hindered their self-care, in addition to making it difficult to adhere to the treatment required concerning their comorbidities. Becker (2017) suggested that telephone contact was an efficient means of health education for this vulnerable population [9], and it appears reasonable to continue with this type of care when aiming to clarify issues and challenges concerning COVID-19. In addition, telehealth was effective in improving glycemic control, blood pressure, and knowledge about type 2 diabetes mellitus in a clinical trial with diabetic and hypertensive elderly individuals [10].…”
Section: Discussionmentioning
confidence: 99%
“…Women comprised 76.7% of our study population. More women have been reported to seek health services [15,16], which may have led to this predominance, as our study population was derived from a specialized health unit database. In one United States study involving patients aged from 18 to 75 years diagnosed with T2DM, a population management program was designed to assist patients with T2DM in self-management through receiving telephone calls and text messages.…”
Section: Discussionmentioning
confidence: 99%
“…The participants in our study had low levels of education, which may have impaired their access to information and hindered their self-care, in addition to making it di cult to adhere to the treatment required concerning their comorbidities. Becker (2017) suggested that telephone contact was an e cient means of health education for this vulnerable population [15], and it appears reasonable to continue with this type of care when aiming to clarify issues and challenges concerning COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Estudo que analisou o efeito de intervenções telefônicas sobre o autocuidado de pessoas diabéticas, indo ao encontro com os achados deste estudo, mostrou que intervenções educativas com esse tipo de estratégia é uma alternativa eficaz para informar aos pacientes sobre os cuidados com o diabetes, auxiliar na diminuição ou manutenção dos níveis de HbA1c e outros parâmetros para função metabólica (8) .…”
Section: Discussionunclassified
“…A intervenção telefônica, como tecnologia em saúde na assistência de enfermagem, pode ser considerada estratégia eficaz à adesão do usuário à prática do autocuidado em pacientes com Diabetes Mellitus, em até mesmo um ano de monitoramento, pois se constatou melhora do autocuidado sobre alimentação adequada, exercício físico regular, abstinência ao tabagismo e etilismo (6) . Além disso, outros estudos evidenciaram que a intervenção telefônica possui impacto positivo na melhora da glico-hemoglobina e do autocuidado em diabetes (7)(8)(9) .…”
Section: Introductionunclassified